Effects of midazolam and flumazenil on ventilation during sustained hypoxia in humans. - Nagyova, B; Dorrington, K; Robbins, P (1993)
The purpose of this study was to investigate whether increases in gamma-aminobutyric acid (GABA) in the brain stem underlie the ventilatory decline observed during hypoxia in man. The ventilatory responses to sustained isocapnic hypoxia were studied in six adult male subjects on three separate days in three pharmacological conditions: (1) without any drug administration; (2) during infusion of midazolam (a drug which potentiates the effect of GABA); and (3) during infusion of flumazenil (a benzodiazepine antagonist). On each experimental day, the following protocol was repeated three times: end-tidal PO2 was held at 100 Torr for 10 min, then at 50 Torr for 20 min and finally at 100 Torr for 5 min. End-tidal PCO2 was held constant throughout. Responses in the three pharmacological conditions were similar. We conclude that neither potentiation of GABA transmission (midazolam) nor antagonism of this potentiation (flumazenil) greatly affect the decline in ventilation which occurs during extended exposure to hypoxia.